EFFECT OF DRYING METHODS ON THE ESSENTIAL OIL COMPONENTS AND ANTIOXIDANT POTENTIAL OF RHIZOMES OF THE SPICE ZINGIBER OFFICINALE ROSCOE.(ZINGIBE RACEAE) - AABHA,; TEWARI, GEETA; PANDE, CHITRA; NEGI, NEETA; BISHT, MAMTA; KANYAL, BHAWANA; SINGH, SHALINI; OM PRAKASH, (The Bioscan, 2023)
Zingiber officinale Roscoe., belonging to the Zingiberaceae family is one of the world’s most popular spices. The aim of the current study was the assessment of drying effects on the essential oil composition of Z. officinale Roscoe. rhizomes that were harvested at the maturity stage from the Betalghat region, Nainital, Uttarakhand. The GC and GC/MS analysis of the oils showed the presence of geranial (18.35-22.26%), neral (13.89-16.43%), β -phellandrene (10.18-11.91%), geraniol (7.25-10.99%), geranyl acetate (3.76-7.74%), camphene (5.36-8.96%), and zingiberene (3.10-5.17%) as the most prevalent components in the oil. All of the samples of essential oils had a high percentage of oxygenated monoterpenes. The amount of neral, β -phellandrene, and camphene increased with all types of drying conditions. α -Pinene, linalool, α -(E, E)-farnesene, and β -sesquiphelland rene were the minor constituents in the oil samples. The results depicted that the oven-dried sample at 30ºC had the highest antioxidant activity and oil yield.